Manifestations of explosive power: Differences in the leg springs between footballers of the different competitive level - Joksimovic, M.; Pavlovic, R.; Pantovic, M.; Eler, N.; Nikšic, E.; Bijelic, S. (European Journal of Physical Education and Sport Science, 2019)
Explosive power is the dominant motoric ability in most sports, regardless of the age, gender and level of the competition, and as such participates in the equations of the specification. Vertical jump (Squat Jump) is a test for estimating the explosiveness of caudal extremities in a number of sports, most often in football, athletics, basketball, volleyball. The study included a sample of 39 respondents (19 cadets, ages 15 ± 0.5 years and 20 juniors, age 17 ± 0.5 years). The aim of this study was to determine the differences in the strength of the leg springs between players of junior and cadet ages. For the estimation of explosive power, the Squat Jump was measured using the Chrono Jump contact mat tensiometric platform (Bosco System, Spain). The analysis of the T-test showed statistically significant differences at the level of p <0.000 in favor of boys of junior age.